REINTEPRATASI AYAT 120 SURAT AL BAQARAH DENGAN PENDEKATAN TOLERANSIF - Abdul Muiz Syaerozi (Al Hikmah: Jurnal Studi Keislaman, 2016)
Many people who believe that Islam is a religion that teaches tolerance values to his people. Theological argument which states Islam is a religion that teaches the values of tolerance to their communities they draw from a Quran and al-Hadith. in the Qur'an many verses that invites his people to be tolerant in religious life. There are at least eighteen verses that directly relate to the significance of the values of tolerance for religious life, among the letters terbeut is verse 30 of Surat al-Naml. Paragraph 120 surat al-Baqarah should not in tafsiri with the interpretations are loaded with cargo intolerance. Because, harfiyyah "لن" within the meaning of the verse does not menunjkkan eternally disclaimer. This verse is also derived in special conditions and situations that the war situation. The meaning of this verse is reminding people not to get caught by his own desires, because, man will never ridla before he follows his own lusts and if it follows his own desires, then the question has become people dzalim. With semikian, this verse does not become a threat to the life of religious tolerance. This verse is also not considered as a verse that teaches hatred or intolerance.